Multi-level responses of oysters Crassostrea virginica for assessing organochlorine pesticides in a Ramsar coastal lagoon in southern Mexico - Vellosa Capparelli, Mariana (2023)
Organochlorine pesticides (OCPs) have been intensively used without proper regulation and control in Latin America due to the prevalence of diseases and pests, thus posing potential risks to nontarget organisms. Initiatives for ecosystem preservation, such as to designate protected areas, may not be enough to avoid contamination by OCPs, considering that protected areas tend to be permeable to diffuse sources. Here, we investigate multi-level responses of the oyster Crassostrea virginica to OCPs in Laguna de Términos, a RAMSAR coastal lagoon in the southern Gulf of Mexico. For this aim, OCPs occurrence and concentrations in the water, sediment, and in oysters from 3 settlement banks were assessed. Enzymatic and non-enzymatic biochemical biomarkers were quantified in the oysters’ mantle and digestive gland, and the human health risk due to oyster consumption was also evaluated. OCPs in water were below detection limits. Fourteen OCPs were detected in sediments (∑OCPs mean of 49 ngg−1) and 7 in oyster tissues (∑OCPs mean of 121 ngg−1). The occurrence of OCPs was related to the land uses along the watersheds of the rivers that drain into the lagoon. Biochemical responses were correlated with OCPs (∑HCH, ∑DDT, heptachlor and endosulfan) in sediment, and oyster tissues. OCPs in oyster tissues showed a strong association with pro-oxidant forces and oxidative stress responses (Superoxide dismutase, Catalase, Glutathione Peroxidase, and lipid peroxidation), and neurotoxicity (Acetylcholinesterase), suggesting that the current OCPs contamination exerts significant stress. Our study also shows that the consumption of oysters from the lagoon increases the potential human health risk. Considering that Laguna de Términos is a protected Ramsar site, we suggest that environmental protection measures should be increased and that a monitoring program for OCPs exposure is necessary to assess the effects on this ecosystem.